Integrated data access, visualization and analysis for Galactic Plane surveys: the VIALACTEA case. Issue Volume 12:Issue S325(2016) (30th May 2017) - Molinari, Sergio; Butora, Robert; Cavuoti, Stefano; Molinaro, Marco; Riccio, Giuseppe; Sciacca, Eva; Vitello, Fabio; Becciani, Ugo; Brescia, Massimo; Costa, Alessandro; Smareglia, Riccardo
Abstract: The VIALACTEA project brings to a common forum the major new-generation surveys of the Milky Way Galactic Plane from 1μm to the radio, both in thermal continuum and in atomic and molecular lines, to attack in a systematic way the characterization of the Milky Way as a star formation engine. Images, catalogues, spectroscopic datacubes and radiative transfer models of the Spectral Energy Distributions (SEDs) of sites of star formation have been incorporated and indexed in the VIALACTEA Knowledge Base (VLKB). The VLKB consists of a combination of a relational database where the VIALACTEA data and metadata are homogenised and stored, and a filesystem-based stored information. This infrastructure allowed, among others, the generation of extensive catalogue for compact sources and extended structures in the Galactic Plane, the implementation of data-mining algorithms for the band-merging of multiwavelength data and expert systems for the automated analysis of molecular line surveys to extract critical kinematical information and derive distances using Galaxy rotation curves and new 3D extinction maps. A new VIALACTEA 3D Visual Analytics interface has been developed that provides integrated access and analysis of continuum and spectroscopic images together with catalogue data directly interfacing with the VLKB.